About Riesz theory of compact operators - Nagendra Pd Sah (Bibechana, 2012)
In this paper, it is shown that every compact operators are bounded and continuous. The bounded and continuous properties of an operator is sufficient for a Riesz operator. For mapping T: K-?I in normed linear space with some extended [1] properties, T becomes compact.